2014
DOI: 10.1108/pijpsm-08-2013-0080
|View full text |Cite
|
Sign up to set email alerts
|

Police officers’ perceptions of the challenges involved in Internet Child Exploitation investigation

Abstract: Purpose – The purpose of this paper is to explore police officers’ perceptions of the challenges and work stressors of working in Internet Child Exploitation (ICE) investigation. Design/methodology/approach – Participants were a heterogeneous sample of 32 ICE investigators across nine Australian jurisdictions. Officers’ perceptions of ICE work were elicited via individual, open-ended, anonymous, telephone interviews, which focused on bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
3

Year Published

2015
2015
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 22 publications
1
29
0
3
Order By: Relevance
“…Finally, community connection (assuming the validity of responsibility as basis for psychological connection to community) and satisfaction with achieving in life could be nurtured by allowing ICE investigators to work autonomously and acknowl-edging the success of ICE investigations within the ICE investigation unit, within the law enforcement community and within the broader community. This practice is supported by research connecting workplace autonomy and work success to increased work-based life satisfaction (Drobnič, Beham, & Präg, 2010;Erdogan, Bauer, Truxillo, & Mansfield, 2012) and improved coping in ICE investigators (Burns et al, 2008;Krause, 2009;Powell et al, 2014aPowell et al, , 2014bWolak & Mitchell, 2009). In contrast, investigators have reported lenient sentencing and low conviction rates of ICE offenders to be sources of strain (Powell et al, 2014a(Powell et al, , 2014b.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Finally, community connection (assuming the validity of responsibility as basis for psychological connection to community) and satisfaction with achieving in life could be nurtured by allowing ICE investigators to work autonomously and acknowl-edging the success of ICE investigations within the ICE investigation unit, within the law enforcement community and within the broader community. This practice is supported by research connecting workplace autonomy and work success to increased work-based life satisfaction (Drobnič, Beham, & Präg, 2010;Erdogan, Bauer, Truxillo, & Mansfield, 2012) and improved coping in ICE investigators (Burns et al, 2008;Krause, 2009;Powell et al, 2014aPowell et al, , 2014bWolak & Mitchell, 2009). In contrast, investigators have reported lenient sentencing and low conviction rates of ICE offenders to be sources of strain (Powell et al, 2014a(Powell et al, , 2014b.…”
Section: Discussionmentioning
confidence: 95%
“…This practice is supported by research connecting workplace autonomy and work success to increased work-based life satisfaction (Drobnič, Beham, & Präg, 2010;Erdogan, Bauer, Truxillo, & Mansfield, 2012) and improved coping in ICE investigators (Burns et al, 2008;Krause, 2009;Powell et al, 2014aPowell et al, , 2014bWolak & Mitchell, 2009). In contrast, investigators have reported lenient sentencing and low conviction rates of ICE offenders to be sources of strain (Powell et al, 2014a(Powell et al, , 2014b. This may suggest that investigators with higher levels of personal control over the conduct of successful investigations would, in addition to experiencing the generally beneficial effects of autonomy and work success, be able to feel a sense of personal responsibility for the connection between effort and success within a context emphasising the community service aspect of ICE investigation.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations